PENINGKATAN HASIL BELAJAR LEMPAR TANGKAP BOLA MELALUI PERMAINAN SEBBOL BAGI SISWA TUNAGRAHITA KELAS II SEKOLAH DASAR DI SEKOLAH LUAR BIASA SLAWI KABUPATEN TEGAL TAHUN PELAJARAN 2013/2014 (Department of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this research is to improve learning outcomes captured throw the ball through the game sebbol for mental retardation students in the elementary school class II Extraordinary School Slawi , Tegal regency . This study uses action research . In the implementation consists of two cycles . Each cycle consists of four stages , namely : planning , implementation , observation , and reflection . The instrument used in this study is the test performance of students and student observation sheet . Based on the results, the percentage of mastery learning outcomes in cycle 1 , psychomotor aspects of 66.67 % , 88.89 % affective aspects , cognitive aspects of 78.79 % , and overall mastery learning students is 72.73 % , or 8 of the total 11 students . In cycle 2 psychomotor aspects of 78.79 % , 90.91 % affective aspects , cognitive aspects of 82.81 % , and overall mastery learning students is 90.91 % or 10 of the total 11 students . In the present study showed an increase in student learning completeness of 18.18 % , from 72.73 % to cycle 1 90.91 % in cycle 2 . Based on the above results , it was concluded that sebbol games can improve learning outcomes for students throw the ball catch for mental retardation students in the elementary school class II Extraordinary School Slawi, Tegal regency.